New Zealand maternity and midwifery services and the COVID-19 response: A systematic scoping review. Issue 3 (May 2022) - Crowther, Susan; Maude, Robyn; Zhao, Ivy Y.; Bradford, Billie; Gilkison, Andrea
Abstract: Problem: COVID-19 guidance from professional and health organisations created uncertainty leading to professional and personal stress impacting on midwives providing continuity of care in New Zealand (NZ). The COVID-19 pandemic resulted in massive amounts of international and national information and guidance. This guidance was often conflicting and not suited to New Zealand midwifery. Aim: To examine and map the national and international guidance and information provided to midwifery regarding COVID-19 and foreground learnt lessons for future similar crises. Methods: A systematic scoping review informed by Arksey and O'Malley's five-stage framework. A range of sources from grey and empirical literature was identified and 257 sources included. Findings: Four categories were identified and discussed: (1) guidance for provision of maternity care in the community; (2) guidance for provision of primary labour and birth care; (3) Guidance for midwifery care to women/wāhine with confirmed/suspected COVID-19 infection, including screening processes and management of neonates of infected women/wāhine (4) Guidance for midwives on protecting self and own families and whānau (extended family) from COVID-19 exposure. Conclusion: Guidance was mainly targeted and tailored for hospital-based services. This was at odds with the NZ context, where primary continuity of care underpins practice. It is evident that those providing continuity of care constantly needed to navigate an evolving situation to mitigate interruptions and restrictions to midwifery care, often without fully knowing the personal risk to themselves and their own families. A key message is the need for a single source of evidence-based guidance, regularly updated and timestamped to show where advice changes over time.